Pandemi Covid-19 Sebagai Alasan Force Majeure Dalam Kontrak Bisnis - Maliq, Alita Aulia; Thahir, Ali; Faliskha, Aulia Najla; Azhari, Fadli; S, Surahmad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The Covid-19 pandemic has severely disrupted various business sectors, including the fulfillment of contractual obligations. Many parties to business contracts faced difficulties in meeting their obligations due to restrictions such as lockdowns and movement limitations. In this context, force majeure has been used as a basis to postpone or adjust contractual obligations. This study aims to analyze the use of force majeure during the Covid-19 pandemic as a basis for deferring business contract obligations and to explore dispute resolution mechanisms resulting from breaches of contract. The research method employed is a literature review, collecting and analyzing relevant sources related to force majeure and dispute resolution mechanisms during the pandemic. The findings indicate that force majeure can be applied as a basis for delaying contractual obligations during the pandemic, though its implementation requires thorough analysis based on contract provisions and evidence of the pandemic’s direct impact. Recommended dispute resolution mechanisms are negotiation and mediation, given their flexibility and efficiency. In conclusion, flexibility and efficient dispute resolution are crucial in addressing contractual challenges during the Covid-19 pandemic.